Magnetic field modelling of machine and multiple machine systems using dynamic reluctance mesh modelling - Yao, Li (2006)
This thesis concerns the modified and improved, time-stepping, dynamic reluctance mesh (DRM) modelling technique for machines and its application to multiple machine systems with their control algorithms. Improvements are suggested which enable the stable solution of the resulting complex non-linear equations. The concept of finite element (FE) derived, overlap-curves has been introduced to facilitate the evaluation of the air-gap reluctances linking the teeth on the rotor to those on the stator providing good model accuracy and efficient computation. Motivated industrially, the aim of the work is to develop a fast and effective simulation tool principally for evaluating salient pole generator system designs including the generator, exciter and the automatic voltage regulator (AVR). The objective is to provide a modelling system capable of examining the detail of machine operation including saturation of main and leakage flux paths, slotting and space harmonics of the windings. Solutions are obtained in a sufficiently short computational time to facilitate efficient iterative design procedures in an industrial design office.